2011
DOI: 10.1177/1074248411429967
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Low Cholesterol is Not Associated With Poor Outcome in Chronic Heart Failure

Abstract: Patients with HF with instrisically low cholesterol levels have a double risk of death up to 5 years compared to patients with pharmacologically induced low cholesterol. Clinicians should not limit the use of statins by fear of lowering the cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
15
2
1
Order By: Relevance
“…The relationship between LDL levels and HF outcomes among the elderly, which we document here, seems to be contradictory to the findings in patients with coronary artery disease [5,6,7,8,9] and in patients enrolled in other HF studies [8,9,11,18,19]. Several studies reported that patients with ischemic and nonischemic HF appear to have an opposite pattern (‘reverse epidemiology'), with low levels being associated with a worse prognosis independent of other prognostic factors [13,20].…”
Section: Discussioncontrasting
confidence: 49%
“…The relationship between LDL levels and HF outcomes among the elderly, which we document here, seems to be contradictory to the findings in patients with coronary artery disease [5,6,7,8,9] and in patients enrolled in other HF studies [8,9,11,18,19]. Several studies reported that patients with ischemic and nonischemic HF appear to have an opposite pattern (‘reverse epidemiology'), with low levels being associated with a worse prognosis independent of other prognostic factors [13,20].…”
Section: Discussioncontrasting
confidence: 49%
“…Statins have clinical benefits on morbidity and mortality in a wide range of diseases and particularly in diabetic patients [14,1819]. Previous experimental studies have explained this positive effect on diabetic hearts by a normalization of RhoA signaling and an increase in NOS3 expression [24,28–29].…”
Section: Discussionmentioning
confidence: 99%
“…High dose of atorvastatin (80 vs 10 mg/day) significantly decreased hospitalization for congestive heart failure [16]. In the perioperative period, statin therapy has been reported to reduce morbidity and mortality, increasingly with high-dose of statins [17,18] whatever cholesterol blood level [13,17,19], suggesting a beneficial pleiotropic cardiovascular effect [12]. In addition, pleiotropic effects of statins decrease mortality in critically ill diabetic patients [4,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Для объяснения неэффективности статинов при ХСН со сниженной ФВ ЛЖ предложены гипотезы коэнзима Q (убихинона), липопротеина эндотоксина и селенопротеи-на [22]. Хотя низкий уровень холестерина ассоциируется с ухудшением исходов у больных с ХСН, он безопасен, если обусловлен приемом статинов [23].…”
Section: Discussionunclassified